MODERNISASI PONDOK PESANTREN DALAM MEMBANGUN MASYARAKAT MADANI (STUDI KASUS PONDOK PESANTREN JAM'IYATUL ULUM SELOGODIG WETAN PROBOLINGGO) - Herwati, Herwati; Ainol, Ainol (STAI Nurul Huda Kapongan Situbondo, 2022)
The modernization of Jam’iyatul Ulum Selogodig Wetan Probolinggo Islamic Boarding School is an approach for long-term solutions to various problems of Muslims today and in the future. Therefore, the modernization of Jam’iyatul Ulum Selogodig Wetan Probolinggo Boarding School is an important part of the birth of modern Islamic civilization. However, the results of the modernization of Jam’iyatul Ulum Selogodig Wetan ProbolinggoIslamic Boarding School cannot be felt in just one or two days, but it requires a long process that will at least take about two generations. As a long process, The modernization of Jam’iyatul Ulum Selogodig Wetan ProbolinggoIslamic Boarding School requires a clear and definite conceptual framework, so that it can lead to ideal Islamic Boarding School. In the last decade, there has been a shift experienced by Islamic Boarding School. The Jam’iyatul Ulum Selogodig Wetan Probolinggo Islamic Boarding School, which is more familiarly known as the JMU, places a high priority on the quality of the students. The implementation of modernization of Islamic boarding schools in building civil society at the Jam’iyatul Ulum Selogodig Wetan ProbolinggoIslamic Boarding School , namely Kiai is no longer the only source of learning. The variety of new learning sources is getting higher, the dynamic of communication between the Islamic Boarding School, education system and other systems allows students to learn from many sources. Almost all Islamic Boarding School provide formal education. There is a need for students to have diplomas and mastery of certain skills. There is a tendency for students to study science and technology. Learn with education costs and living costs in each month or quarter. Seeing the historical background and typology of Islamic Boarding School, the characteristics and dynamics of the development of pesantren as a unique Islamic educational institution will directly or indirectly face the challenges of the times. The development of science has become an integral part in the efforts of Islamic boarding schools to respond to the challenges of the times.